Influence of ISDN, l-NAME and selenium on microcirculation, leukocyte endothelium interaction and angiogenesis after frostbite. Issue 1 (February 2015) - Goertz, O.; Haddad, H.; von der Lohe, L.; Lauer, H.; Hirsch, T.; Daigeler, A.; Lehnhardt, M.; Kolbenschlag, J.
Abstract Background The body of knowledge regarding the different facets of frostbite injury continues to expand. However, beside the administration of physiological saline, local rewarming, local disinfection and symptomatic medications, today no causal therapy is known which would accelerate angiogenesis and wound healing. The aim of this study was to investigate the influences of dilative acting drugs on microcirculation, angiogenesis and leukocyte behavior. Materials and Methods Ears of male hairless mice (n = 40) were inflicted with full thickness frostbites using a cold air jet. Then the affects of four intraperitoneal injections of isosorbitdinitrate (ISDN, n = 10), l-nitroarginine-methyl-ester (l-NAME, n = 10), selenium (n = 10) or sodium chloride (n = 10; each administered to one of four corresponding study groups), on microcirculation, leukocyte-endothelial interaction and angiogenesis were investigated over a 12-day period using intravital fluorescent microscopy. Results Angiogenesis was most improved by ISDN (36.8 vs. 54.5% non-perfused area on day 3, 3.9 vs. 17.0% on day 7 compared to selenium, p < 0.006). Venular diameter was most significantly dilated in the ISDN-group, l-NAME showed significantly decreased diameter over the complete time of 12 days. ISDN had positive influences on edema formation, which was significantly reduced compared to control (27% lower values compared to control; p = 0.007 on day 3). The l-NAME-group showed the significant highest leukocyte-adhesion compared to control on days 7 and 12 (53% resp. 58% higher, p < 0.006). Conclusion Overall, out of all the drugs tested, ISDN improved angiogenesis, dilated venules and decreased edema formation and therefore seems to have the greatest positive impact on these crucial parameters after frostbite injury.